2014
DOI: 10.1073/pnas.1413018111
|View full text |Cite
|
Sign up to set email alerts
|

An intramolecular lock facilitates folding and stabilizes the tertiary structure of Streptococcus mutans adhesin P1

Abstract: The cariogenic bacterium Streptococcus mutans uses adhesin P1 to adhere to tooth surfaces, extracellular matrix components, and other bacteria. A composite model of P1 based on partial crystal structures revealed an unusual complex architecture in which the protein forms an elongated hybrid alpha/polyproline type II helical stalk by folding back on itself to display a globular head at the apex and a globular C-terminal region at the base. The structure of P1's N terminus and the nature of its critical interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…The tertiary structure and cell surface architecture of P1 has been studied extensively [20,[36][37][38][39]. Interestingly, C123, which we demonstrate herein to represent the amyloidforming portion of P1, also associates with covalently attached full-length P1 on the cell surface [39].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The tertiary structure and cell surface architecture of P1 has been studied extensively [20,[36][37][38][39]. Interestingly, C123, which we demonstrate herein to represent the amyloidforming portion of P1, also associates with covalently attached full-length P1 on the cell surface [39].…”
Section: Discussionmentioning
confidence: 65%
“…Because an S. mutans sortase-deficient mutant is defective in amyloid formation [19], an additional sortase substrate, GbpC, which was not identified in our initial screen but demonstrated high amyloid prediction scores by computational analyses [34,35], was also evaluated in these experiments. Unlike the proteins listed above, for which little structural information is available at present, the complete tertiary structure of P1 has been modelled based on crystal structures of several partial polypeptides [36][37][38]. Importantly, it is now recognized that the C-terminal region of P1 exists in two separate forms: firstly, in the context of the full-length molecule where it is positioned in proximity to the cell wall, and secondly, as a naturally processed and isolated C123 polypeptide that associates with covalently attached fulllength P1 on the cell surface [39].…”
Section: Resultsmentioning
confidence: 99%
“…The stalk is generated by a high affinity interaction between the ␣-helix and polyproline II (PPII)-helices of the A and P domains, respectively, serving to present the V "head" domain at its tip (9). The N terminus forms a stabilizing scaffold by wrapping behind the base of the stalk (10). Crystal structures of the V regions of SpaP and SspB have revealed a common architecture consisting of a lectin-like fold with a putative binding cleft (11,12).…”
mentioning
confidence: 99%
“…The A-repeats form a long ␣-helix that intimately intertwines into a left-handed supercoiled structure with the helical polyproline P-repeats to form the stalk (45) The C-terminal region is also globular and comprises three structurally related ␤-sandwich domains stabilized by covalent isopeptide bonds (44,47). The crystal structure of the N terminus of P1 in complex with its C-terminal intramolecular binding partner revealed that it forms a novel stabilizing scaffold at the base of the stalk that contributes to the stability and proper folding of the full-length molecule (48). Numerous monoclonal antibodies (mAbs) targeting different domains of P1 have been generated and characterized, providing powerful molecular probes of the highly complex protein structure (6, 49 -51) (see Fig.…”
mentioning
confidence: 99%